Clinical Accuracy of Instrument-Read SARS-CoV-2 Antigen Rapid Diagnostic Tests (Ag-IRRDTs) - Keskin, Ali Umit; Ciragil, Pinar; Topkaya, Aynur Eren (International Journal of Microbiology, 2022)
This systematic review (PROSPERO registration number: CRD42021282476) aims to collect and analyse current evidence on real-world performance based on clinical accuracy of instrument-read rapid antigen diagnostic tests (Ag-IRRDTs) for SARS-CoV-2 identification. We used PRISMA Checklist and searched databases (PubMed, Web of Science Core Collection and FIND) for publications evaluating the accuracy of SARS-CoV-2 Ag-IRRDTs as of 30 September 2021, and included 40 independent clinical studies resulting in 48 Ag-IRRDT datasets with 137,770 samples. Across all datasets, pooled Ag-IRRDT sensitivity was 67.1% (95% CI: 65.9%–68.3%) and specificity was 99.4% with a tight CI. Pooled sensitivity and specificity of SARS-CoV-2 Ag-IRRDTs did not demonstrate a significant superiority over SARS-CoV-2 rapid antigen tests which do not require a reader instrument, even in the case where surveillance and screening datasets were excluded from the analysis. Nevertheless, they provide connectivity advantages and remove operator interface (in results-reading) issues. The lower sensitivity of certain brands of Ag-IRRDTs can be overcome in high prevalence areas with high frequency of testing. New SARS-CoV-2 variants are major concern for current and future diagnostic performance of these tests.